Unprecedentedly high activity and selectivity for hydrogenation of nitroarenes with single atomic Co1-N3P1 sites - Jin, Hongqiang; Li, Peipei; Cui, Peixin; Shi, Jinan; Zhou, Wu; Yu, Xiaohu; Song, Weiguo; Cao, Changyan (Nature communications, 2022)
Transition metal single atom catalysts (SACs) with M 1 -N x coordination configuration have shown outstanding activity and selectivity for hydrogenation of nitroarenes. Modulating the atomic coordination structure has emerged as a promising strategy to further improve the catalytic performance. Herein, we report an atomic Co 1 /NPC catalyst with unsymmetrical single Co 1 -N 3 P 1 sites that displays unprecedentedly high activity and chemoselectivity for hydrogenation of functionalized nitroarenes. Compared to the most popular Co 1 -N 4 coordination, the electron density of Co atom in Co 1 -N 3 P 1 is increased, which is more favorable for H 2 dissociation as verified by kinetic isotope effect and density functional theory calculation results. In nitrobenzene hydrogenation reaction, the as-synthesized Co 1 -N 3 P 1 SAC exhibits a turnover frequency of 6560 h −1 , which is 60-fold higher than that of Co 1 -N 4 SAC and one order of magnitude higher than the state-of-the-art M 1 -N x -C SACs in literatures. Furthermore, Co 1 -N 3 P 1 SAC shows superior selectivity (>99%) toward many substituted nitroarenes with co-existence of other sensitive reducible groups. This work is an excellent example of relationship between catalytic performance and the coordination environment of SACs, and offers a potential practical catalyst for aromatic amine synthesis by hydrogenation of nitroarenes. Modulating the atomic coordination structure has emerged as a promising strategy to further improve catalytic performance. Here, the authors report an atomic Co1/NPC catalyst with unsymmetrical single Co1N3P1 sites that displays high activity and chemoselectivity for hydrogenation of functionalized nitroarenes.